Effects of Immunostimulants on Physiological Performances, Immune Gene Expression, Liver, and Intestinal Protection Against Vibrio parahaemolyticus Infection in Juvenile Asian Seabass (Lates calcarifer) - Yun Liu; Qian-Qian Chen; Victor Charlie Andin; Wei-Kang Chor; Chou-Min Chong; Po-Tsang Lee; Crystale Siew-Ying Lim; Jiun-Yan Loh (Aquaculture Nutrition)
The present study aims to develop a more valuable innovative aquaculture feed for the sustainable Lates calcarifer aquaculture industry. An experiment with a completely random design was developed with five groups containing 0% immunostimulant and 0.5% ginger, 1.0% garlic, 0.15% palm carotene alone or in combination. Each diet was randomly assigned to triplicate groups of 30 fish (10.06 ± 0.09 g) per tank. The fish were fed once daily to apparent satiation. Throughout the 56-day feeding trial, the results suggest that although no significant differences were observed among almost all experimental groups in growth performance, feed efficiency, fish composition and disease resistance, the palm carotene supplementations downregulated intestinal tumor necrosis factor alpha (TNF-α) and interleukin (IL)-6 expression, decreased sum scores of liver pathological changes, increased intestinal villus surface (VS) compared with the control group. Moreover, the combined treatment shows more promising immune gene expression (intestinal IL-1 beta (IL-1β) was also downregulated compared to the control), liver and intestinal protection (lower sum scores of liver pathological changes and larger intestinal VS than palm carotene alone supplementation, goblet cell (GC) number per intestinal villus was also increased compared to the control) effects on L. calcarifer infected with Vibrio parahaemolyticus. Therefore, a combination of 0.5% ginger, 1.0% garlic, and 0.15% palm carotene in the diet of L. calcarifer can be used as an immune booster due to fishmeal substitution to obtain better immunocompetence.